Faculty Development Program In India: Identifying Gaps And Opportunities For Reforms: Faculty Development Program In India: Identifying Gaps And Opportunities For Reforms - Dr. Shubhada Gade (National Journal of Integrated Research in Medicine, 2020)
Faculty Development Programs in India can be traced from NTTC till National Faculty Development program of MCI being implemented since 2009 which is a mandatory workshop. But there is a gap between the Faculty Development Programs and its impact on medical teacher’s behaviour at their workplace. Utility of the Faculty Development Program in terms of transfer of knowledge and in generating evidences about the Medical education process is not well established because evaluation of Faculty Development Programs for their impact analysis is not well studied. This manuscript highlights the importance of evaluation of utility and the impact of Faculty Development Programs on the personal and institutional growth. First and foremost there is a need for timely intervention to evaluate the effectiveness & impact of the Faculty Development Programs Operational utilization of the evidence based outcome towards suitable and appropriate policy intervention should be found out to make the faculty development programme well focused and well directed to the relevant needs, concerns and challenges of need to restructure the Faculty Development Program for its content. A hypothesis for the evaluation of the impact & effectiveness of the Faculty Development Program for its Upgradation & strengthening should be generated. [Gade S Natl J Integr Res Med, 2020; 11(4):72-78]